KRISIS IKLIM, GENDER, DAN KERENTANAN: POTRET PEREMPUAN PETANI DI KABUPATEN KARANGANYAR, JAWA TENGAH - Al Farisi, Muhammad Salman; Alfirdaus, Laila Kholid (Journal of Politic and Government Studies, 2020)
Learning from the experiences of women farmers in Kaliboto Village, Mojogedang, Karanganyar Regency, this paper disusses the gender dimensions of climate crisis which causes vulnerabilities, including to women farmers. Despite the previous numerous studies about climate crisis in Indonesia, it is unfortune to see that climate issues are centralized on technical paradigm instead of being seen as a political problem in general. Hence, this study focuses on how gendered-vulnerability happen and can be explained through power relations which politically exist among women farmers. To answer those questions, the researcher uses a qualitative method through interviews, literature and documentation analysis, and academic discussion. This research found that women farmer’s vulnerability is a real problem which exists in the society. Women farmers are often weak and weakend in terms of adaptation capability in any level of society, including limited access to some resources that have worsen their capability to strengthen resilience. The vulnerbalities that have been found regarding the impact of climate crisis are the needs of water for crops and households, labor absorption and revenue-stream, limitation of knowledges, roles, and public participation for women farmers in climate crisis era